3D Drone Mapping - Ansari, Aman; Sah, Binay; Dhungel, Hasina; Gautam, Darshan (Journal of Innovative Image Processing, 2023)
A major portion of the earth remains unexplored today. There are many reasons for this. One of them is because those places are or maybe dangerous for the explorers. Also, Nepal and many other under-developed countries buy satellite images and maps of their territory from other countries. The problem with these maps is that they are not always up-to-date and are very low-resolution images. In order to solve these problems, this research work has designed a quadcopter (four propellers) drone with HD camera. This device is capable of capturing images with colour, intensity, and depth values at each pixel so that a 3D map can be constructed. Unmanned Aerial Vehicles (UAVs) also called Drones can be designed for numerous objectives and tasks. This article intends to design a drone capable of creating its own pathway and taking flight autonomously. During the flight, the UAV is programmed to capture high-resolution images at regular intervals with 60-80% overlap. The overlap between images is highly necessary to obtain numerous data of the same point, which will be beneficial in creating a finer 3D map. The 3D map is generated by using a process called photogrammetry, which takes pictures as input and displays a 3D map as output by utilizing the data present in pictures. This drone can be used to capture pictures and create 3D maps of unexplored areas like caves, volcano craters, etc. Also, high-resolution pictures can be merged and uploaded for satellite imaging applications. Besides, the same vehicle can be used for many other applications like forest fire monitoring systems, endangered wildlife monitoring, surveying, and so on with slight alterations.
Keywords: Drones; UAV; Photogrammetry; Propellers; Pixels; QuadCopter; Digital Elevation Model (DEM)